ORGANISATIONAL LEADERSHIP CHALLENGES IN ADOPTING DEVOPS IN NORTHERN NIGERIA SMES - Usman Hamza; Nasuha Lee Abdullah; Sharifah Mashita Syed-Mohamad (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The development and operation issue is rapidly expanding as some organisations in northern Nigeria seek to capitalise on the benefits it can provide to software development organisations and information technology projects. Adopting DevOps, on the other hand, requires significant organisational change, especially where tradition and established processes exist. This study presents the findings of a five-month qualitative diary study following the implementation of DevOps in a Nigerian SME with over 100 employees as part of a large-scale doctoral research project that investigates software development processes and leadership challenges. Based on the study’s findings, the case study organisation employs the DevOps approach to develop new software for internal and external use. DevOps appears to be well-known in theory, but it is extremely difficult to put into practise. This difficulty is exacerbated by the need to maintain old systems, a lack of technical leadership, management systems, and resilience. This research also found evidence of job creation, particularly among software developers. Taken together, we argue that DevOps is an interdisciplinary topic that requires all stakeholders to participate in order to communicate and collaborate, and that it would benefit greatly from more leadership and possibly deeper psychological research.